2013
DOI: 10.1007/s12640-013-9440-1
|View full text |Cite
|
Sign up to set email alerts
|

1MeTIQ Provides Protection Against Aβ-Induced Reduction of Surface Expression of Synaptic Proteins and Inhibits H2O2-Induced Oxidative Stress in Primary Hippocampal Neurons

Abstract: Alzheimer’s disease (AD) is associated with increased brain levels of β-amyloid (Aβ) peptides, which readily self-aggregate into fibrils and oligomers that have particularly deleterious properties towards synapses of excitatory glutamatergic neurons. Here, we examined the neuroprotective effects of 1-methyl-1,2,3,4,-tetrahydroisoquinoline (1MeTIQ) against Aβ-induced loss of synaptic proteins in cultured primary hippocampal neurons. Exposure of mature primary hippocampal neurons to 10 μM synthetic Aβ1-40 over 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In addition, 1MeTIQ reduced H 2 O 2 -induced ROS production in immature hippocampal neuronal cultures. All in vitro results support the hypothesis that 1MeTIQ is an NMDAR antagonist with strong antiradical activity (Kuszczyk et al 2014). Moreover, it was demonstrated that 1MeTIQ inhibited the binding of radioactive [ 3 H]MK-801 to isolated brain membranes (Antkiewicz-Michaluk et al 2006).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, 1MeTIQ reduced H 2 O 2 -induced ROS production in immature hippocampal neuronal cultures. All in vitro results support the hypothesis that 1MeTIQ is an NMDAR antagonist with strong antiradical activity (Kuszczyk et al 2014). Moreover, it was demonstrated that 1MeTIQ inhibited the binding of radioactive [ 3 H]MK-801 to isolated brain membranes (Antkiewicz-Michaluk et al 2006).…”
Section: Discussionsupporting
confidence: 77%
“…Second, there is evidence that 1MeTIQ protects the activity of NADH-ubiquinone oxidoreductase enzyme, suppresses the inhibition by MPP + of mitochondrial respiratory complex I and thus prevents the ROS-mediated neurotoxic effect of MPP + (Parrado et al 2000). Third, 1MeTIQ is an NMDAR antagonist and may indirectly inhibit excitotoxicity-evoked ROS production (Kuszczyk et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms of how oxidative stress and neuroinflammation impair learning and memory capacity remain unclear, disruption or loss of synapse might be one of the reasons. It's reported that H 2 O 2 induced by Aβ, the main component of plaque in AD, is capable of inducing reduction of synaptic proteins and loss of synapse, which is implicated in Aβ-induced cognitive deficits [64], [65]. Furthermore, in mouse AD models, inhibition of oxidative stress and neuroinflammation attenuates synaptic loss and cognitive dysfunction [66].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of synaptic protein expression was performed similarly to a previously published method, with modi cations [39]. After immuno uorescence staining for PSD95 and synaptophysin, elds were selected randomly using the guidance of DAPI nuclear staining (three images/treatment group, total 9 images from three independent experiments), then confocal images were taken.…”
Section: Expression Of Synaptic Proteinsmentioning
confidence: 99%